Digital economy and logistics as new areas of study in Higher Education; Opcion; Vol. 36, № 26 (SI) - Kabanov O. V. Oleg Vladimirovich; Starostina Ju. E. Julia Evgenievna; Nazarova L. N. Lionella Nikolaevna; Yakimova T. B. Tatiana Borisovna; Govorkov A. S. Aleksey Sergeevich; Tsvetkova I. I. Izabella Ivanovna; Prasolov V. I. Valery Ivanovich (2020, 2020)
Title screen